Mapping of records-keeping practices of selected private educational institutions in Metro Manila towards the creation of a classification and filing guide for Saint Poveda College - Asuncion, Emelita B. (2015)
This study focused on the prevailing records-keeping practices of selected private educational institutions in Metro Manila to be able to come up with an effective classification and filing guide for Saint Pedro Poveda College (SPPC) based on the concept of International Standard on Archival Description better known as ISAD(G). St. Scholastica's College Manila, St. Paul University and St. Mary's College in Quezon City and Saint Pedro Poveda College are the schools surveyed for this study.